2012
DOI: 10.1136/bmjopen-2012-001340
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin Card Sorting Test scores and clinical and sociodemographic correlates in Schizophrenia: multiple logistic regression analysis

Abstract: ObjectivesThis study investigated what clinical and sociodemographic factors affected Wisconsin Card Sorting Test (WCST) factor scores of patients with schizophrenia to evaluate parameters or items of the WCST.DesignCross-sectional study.SettingPatients with schizophrenia from three hospitals participated.ParticipantsParticipants were recruited from July 2009 to August 2011. 131 Japanese patients with schizophrenia (84 men and 47 women, 43.5±13.8 years (mean±SD)) entered and completed the study. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…CAT: HC ¼4 70.4, SCZr 10 years¼ 2.8 7 0.7, SCZ4 10 years¼ 1.7 7 0.8; PR: HC¼ 30.17 3.5, SCZr 10 years ¼36.1 77.6, SCZ410 years ¼66.8 7 10.8; PE: HC¼ 24.2 7 3, SCZ r 10 years¼ 38.5 7 6.9, SCZ410 years ¼45.9 7 11. our findings, we have additionally provided the effect sizes of our results, which were considered moderate to large. Finally, in contrast to other studies (Banno et al, 2012), our results failed to show an impact of cognitive impairment on severity of symptoms or on global functioning. This lack of association highlights the effect of DoI on GMV differences, which are not influenced by differences in symptoms or functioning.…”
Section: Clinical Characteristics and Behavioral Performancecontrasting
confidence: 85%
See 1 more Smart Citation
“…CAT: HC ¼4 70.4, SCZr 10 years¼ 2.8 7 0.7, SCZ4 10 years¼ 1.7 7 0.8; PR: HC¼ 30.17 3.5, SCZr 10 years ¼36.1 77.6, SCZ410 years ¼66.8 7 10.8; PE: HC¼ 24.2 7 3, SCZ r 10 years¼ 38.5 7 6.9, SCZ410 years ¼45.9 7 11. our findings, we have additionally provided the effect sizes of our results, which were considered moderate to large. Finally, in contrast to other studies (Banno et al, 2012), our results failed to show an impact of cognitive impairment on severity of symptoms or on global functioning. This lack of association highlights the effect of DoI on GMV differences, which are not influenced by differences in symptoms or functioning.…”
Section: Clinical Characteristics and Behavioral Performancecontrasting
confidence: 85%
“…We can speculate that these differences may be secondary to the different temporal subdivision within the patient groups compared with that in the present study (i.e., 10 years). Other studies found an effect of the duration of illness in determining the number of perseverative responses (Bellino et al, 2004) and the "difficulty to maintain set", another WCST performance measure (Banno et al, 2012). A meta-analysis (Johnson-Selfridge and Zalewski, 2001) of executive functioning in patients with schizophrenia did not uncover any significant effect for DoI on behavioral performance.…”
Section: Clinical Characteristics and Behavioral Performancementioning
confidence: 96%
“…The WCST 28 mainly assesses executive function including cognitive flexibility in response to feedback. We used a modified and computerized version of the WCST, the (Keio Version) (KWCST) 29 30 31 . The outcome measures were the numbers of categories achieved (CA), total errors (TE), and perseverative errors of Milner (PEM) and Nelson types (PEN) in the first trial.…”
Section: Methodsmentioning
confidence: 99%
“…Differences between COMT and 5-HT1A-R genotypes and WCST performances (number of perseverative errors) at baseline were analysed by means of analysis of covariance (ANCOVA), with age and number of years of education as covariates, since these variables were found to influence WCST performances in schizophrenia (Banno et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%